2010
DOI: 10.1007/s12035-010-8108-6
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Phospholipases A2 in Mammalian Brain and Neural Cells: Roles in Functions and Dysfunctions

Abstract: Several "low molecular weight" or "secretory" phospholipases A(2) isoforms may be expressed in mammalian neural cells. Indeed, mRNAs for GIB, GIIA, GIIE, GIII, GV, GX, and GXII were detected in brain tissues despite different levels. However, only the presence of GIB, GIIA, and GV proteins has been clearly demonstrated in neural cells or in the nervous tissue. Although the roles of GIB and GV in the nervous tissue are still elusive, there is evidence to support the involvement of GIIA in physiological and path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 179 publications
(207 reference statements)
1
11
0
Order By: Relevance
“…GIB, GIIA, GIIC, GIID, GIIE, GIIF, GIII, GV, GX and GXII) and their structural and functional properties have been recently reviewed [13]. The present study demonstrates that treatment of PC12 cells with NGF causes a time-dependent change in the subcellular localization of endogenous GIIA, one of the sPLA 2 isoforms expressed by this cell type and present in most mammalian brain areas.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…GIB, GIIA, GIIC, GIID, GIIE, GIIF, GIII, GV, GX and GXII) and their structural and functional properties have been recently reviewed [13]. The present study demonstrates that treatment of PC12 cells with NGF causes a time-dependent change in the subcellular localization of endogenous GIIA, one of the sPLA 2 isoforms expressed by this cell type and present in most mammalian brain areas.…”
Section: Discussionsupporting
confidence: 50%
“…Several reports have suggested that Ca 2? -dependent low molecular weight PLA 2 s, generally referred to as ''secretory'' (sPLA 2 ) may be involved in neuritogenesis [9][10][11][12][13]. The assumption that sPLA 2 isoforms are involved in neurite outgrowth derives both from studies in which cultured cells were exposed to exogenous enzymes from fungi [14], insect [12], snake venoms [15] and from studies in which the specific isoform group X sPLA 2 (GX), was overexpressed in PC12 cells [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…sPLA 2 enzymes are implicated in lipid mediator release(52), degranulation (52), cellular proliferation (52), destruction of invading bacteria (52), viruses (41,49) and activation of intracellular signaling cascades (42). GX-sPLA 2 is expressed in alveolar macrophages and epithelial cells in the lungs of patients with pneumonia (46), neuronal cells (29), male reproductive organs (22) and atherosclerotic plaques (39), and is cleaved to its active form in inflamed tissues (45). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the latest findings on the oncogenic action of PLA 2 in prostate cancer and its association with neurological disease offers further motivation for finding new modulators of its function. [9,10] The marine environment is a rich source of molecules endowed with anti-PLA 2 properties, a number of which have shown potent and selective in vitro and in vivo anti-sPLA 2 activity. [11][12][13] One of the most widespread groups of constituents found in sessile organisms with a typical selective profile against secretory PLA 2 are the sesquiterpenes bearing a g-hydroxybutenolide ring, whose reference compound is manoalide.…”
Section: Introductionmentioning
confidence: 99%